Effect of the In-Office Bleaching on the Shear Bond Strength of Orthodontic Brackets. - Khudair A AL-Jumaili; Omar Kh.M. Thiab (Al-Rafidain Dental Journal, 2011)
Aims: To evaluate the effect of In-Office enamel vital bleaching with (35% H2O2) and the effect of immersion in artificial saliva following bleaching on the shear bond strength of titanium orthodontic brackets bonded with an orthodontic composite adhesive. Materials and Methods: The samples of the study were categorized into three main groups; bleaching, immersion and control group. Each group was consisted of 10 teeth (Human upper right first premolars). Specimens in bleaching group were bonded immediately after bleaching; immersion group specimens were bleached, then immersed in artificial saliva and held for 1 month before bonding. All specimens were bonded with titanium orthodontic brackets (ROTH, slot size 0.018 inch). The shear bond strength was measured by using the unconfined shear testing machine. Results: Bleaching group had the lowest shear bond strength whereas the control group had the highest one. No significant differences were noted between the immersion and control group (at p ≤ 0.05). Conclusions: In-Office enamel bleaching was significantly reduced the shear bond strength of orthodontic brackets. Immersion in artificial saliva (following bleaching) was able to improve the reduced shear bond strength.